Research on Optimization of Coal Pressure Relief Borehole Parameters under High-Stress Conditions - Heng Zhang; Tie Li; Zhenhua Ouyang; Su Liu; Haiyang Yi (Geofluids)
Determining the parameters of boreholes drilled for relieving pressure in coal seams is the key preventing and controlling rock bursts in boreholes of large diameter. In this study, theoretical analysis, numerical simulation, literature research, and other analysis methods are applied to study the angles of elastic energy dissipation and stress transfer, the distribution law of the pressure relief area, and the areas of stress concentration, energy, stress, displacement, and plastic behavior of large-diameter pressure relief boreholes in coal seams under high-stress conditions. The results are then used to evaluate the relationship between large-diameter pressure relief boreholes and the borehole arrangement. The following results are obtained. (1) A large-diameter results in a large amount of elastic energy released by the surrounding coal, low residual elastic energy density, strong interaction between boreholes, large pressure relief range of the borehole, and high pressure relief efficiency. (2) The main evaluation factor of the borehole pressure relief effect is its thickness and stress concentration area; secondary evaluation is based on the areas of energy, displacement, stress, and plastic behavior. (3) Six evaluation index systems are established to evaluate the effects of borehole pressure relief, which are found to be the thicknesses of the borehole pressure relief area and stress concentration area, reduction degree of energy density, percentage of stress reduction, displacement, and penetration degree of the plastic area. (4) It is determined that when the diameters of the pressure relief boreholes are 100, 120, 180, and 200 mm, a single-row borehole arrangement is adopted; a three-pattern borehole arrangement is adopted with diameters of 140 and 160 mm. These research results can provide theoretical support in selecting reasonable borehole arrangements for pressure relief boreholes of different diameters.